Academic Mentoring Nature-Nurture Cycle: Some Insights from Own Experience - Evans Osabuohien; Alhassan Abdul-Wakeel Karakara (African Governance and Development Institute (AGDI), 2023)
In this little article, we discuss our experience and relationship as a mentor (Evans Osabuohien) and mentee (Alhassan Karakara) and useful insights gained over the mentorship period of five years. This becomes essential following various discussions we have had at different academic for a notably conferences, seminars, and workshops. The discourse is mainly focused on the areas of conducting research, scholarly publication, and administering research grants. We underscore three points to help mentors and mentees to establish a good working relationship in the mentoring process drawing from our experience as social scientists, which would also be applicable in other disciplines.
Keywords: 330; Academic research mentoring; Academic publication mentoring; Research grant mentoring